PEMANFAATAN MODAL SOSIAL BAGI KELUARGA NELAYAN MISKIN DI MASA PANDEMI COVID-19 (Nelayan Miskin Nagari Painan Selatan Kabupaten Pesisir Selatan Provinsi Sumatera Barat) - Rinaldi Eka Putra; M. Fedro Syafiola; Feri Hidayat Suri (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2023)
This study aims to find out how poor fisherman families survived during the pandemic in Painan, Pesisir Selatan Regency, West Sumatra province. This research uses a qualitative approach, with theory as its unit of analysis. Through the studies that have been carried out, it is known that various ways of survival for families who went to sea on the south coast during the pandemic, it is known that the pillars of the capital triangle, which include intermediary relations and social networks with various components, can all come together. build mutually exclusive fishing groups. During the Covid-19 pandemic, this trust Association is the foundation for the use of social capital in the practice of Group life in fishing communities, this is evidenced by the existence of informal institutions that affect people's lives